2022
DOI: 10.3390/polym14122325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Different Polymer and Composite Abutments on the Color Accuracy of Multilayer Pre-Colored Zirconia Polycrystal Dental Prosthesis

Abstract: With increasing aesthetic awareness and emphasis on time costs in today’s society, monolithic multilayer precolored zirconia ceramics (M-Zr) facilitate aesthetic restorations in a convenient and straightforward manner without the need for veneering porcelain to modify the color. However, the effect of abutment materials on the final color of M-Zr remains unclear. Herein, we placed Vita A1 Shade M-Zr on six different abutment materials, zirconia (Y-TZP), 3D printed composite resin (CR), dental model resin (MR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Computer-aided design/manufacturing (CAD/CAM) is widely accepted by dentists and dental technicians because of its precision and efficiency [ 7 , 8 ]. As the requirements of the fully digital workflow, accompanied by oral scanning, have increased, the demand for multilayer transparency and gradient-color “monolithic zirconia restorations” that do not require veneering has increased [ 8 , 9 , 10 ]. The main weaknesses of zirconia are its unsatisfactory clinical bonding performance and evidence from long-term follow-up studies showing that the bond between zirconia and dental cement is poorer than that of lithium disilicate (LD) glass-ceramics [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Computer-aided design/manufacturing (CAD/CAM) is widely accepted by dentists and dental technicians because of its precision and efficiency [ 7 , 8 ]. As the requirements of the fully digital workflow, accompanied by oral scanning, have increased, the demand for multilayer transparency and gradient-color “monolithic zirconia restorations” that do not require veneering has increased [ 8 , 9 , 10 ]. The main weaknesses of zirconia are its unsatisfactory clinical bonding performance and evidence from long-term follow-up studies showing that the bond between zirconia and dental cement is poorer than that of lithium disilicate (LD) glass-ceramics [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hsu et al [28] showed that using PAEK (PEEK & PEKK), as a substrate material was deduced to have the best color accuracy (ΔE < 2.9), among all the specimens tested in the present study. The results of various color attributes show that PAEK materials have a better color balance, higher color saturation, and lower hue compared to those of the other groups.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have reported that the final color of highly translucent zirconia is influenced by the background color. For instance, Hsu et al [ 37 ] and Tabatabaian et al [ 38 ] indicated that different abutment colors provided different TP and ΔE values as well as color attributes. Consistent with these findings, various research has suggested a minimum thickness of 1 mm for color accuracy on a light color background and a minimum thickness of 1.5 mm for the optimal masking ability [ 15 , 39 , 40 ], consistent with the results of this study which determined distinct color attributes at 1 mm thickness compared to other thicknesses.…”
Section: Discussionmentioning
confidence: 99%